Molecular pathways leading to sleep and wakefulness in Drosophila - Christodoulou, K (2021)
Sleep is a universal and highly conserved phenomenon across species; yet its operational mechanisms remain one of the greatest biological mysteries. In Drosophila, sleep homeostasis is largely mediated by the activity of neurons projecting to the dorsal fan-shaped body (dFB). Dopamine promotes wakefulness by inhibiting the activity of dFB neurons, switching them to a silent state. This wake-promoting effect is hypothesised to require the exocytosis of the potassium “leak” channel, Sandman, to the plasma membrane, where it exerts its effects by blunting the firing of the neurons. In the chronically sleep-deprived flies bearing a mutation for the crossveinless-c (cv-c) gene, the dFB neurons were previously found in electrical quiescence as well. It is therefore possible that in these mutants, Sandman resides at the plasma membrane of the neurons, reducing their excitability and causing insomnia in the flies. However, the signals responsible for Sandman’s recycling to and from the plasma membrane remain elusive.